Ion track template technique for fabrication of ZnSe2O5 nanocrystals - Akilbekov, Abdirash T.; Akylbekova, Aiman; Usseinov, Abay; Kozlovskiy, A. L.; Baymukhanov, Z.; Giniyatova, Sh G.; Popov, Anatoli I.; Dauletbekova, Alma (Elsevier B.V., 2020)
ZnSe2O5 nanocrystals with an orthorhombic structure were synthesized by electrochemical deposition into a-SiO2/n-Si ion track template formed by 200 MeV Xe ion irradiation with the fluence of 107 ions/cm2. The lattice parameters determined by the X-ray diffraction and calculated by the CRYSTAL computer program package are very close to each other. It was shown that ZnSe2O5 has a direct band gap of 2.8 eV at the Γ-point. In addition, the calculated charge distribution and chemical bonds show that the crystal has an ion-covalent nature. The photoluminescence excited by photons at 300 nm has a low intensity arising mainly due to zinc and oxygen vacancies.
The work was performed under the grant of the Ministry of Education and Science of the Republic of Kazakhstan AP05134367 and Latvian grant lzp
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Ion track; ZnSe2O5; Track template; Luminescence; Ab initio